Hamstring Anterior Cruciate Ligament Reconstruction Using an Adjustable-Loop Cortical Suspension Device: Immediate Postoperative Magnetic Resonance Imaging - Choi, Nam-Hong; Lee, Seung-Joo; Oh, Whang-Kyun; Victoroff, Brian N. (The Journal of Knee Surgery, 2019)
The purpose of this study is to determine whether the hamstring grafts are fully inserted into the femoral tunnel with the adjustable loop using immediate postoperative magnetic resonance imaging (MRI) after anterior cruciate ligament (ACL) reconstructions. A total of 62 consecutive patients underwent hamstring ACL reconstruction using an adjustable-loop cortical suspension device for the femoral fixation and the Intrafix sheath and screw for the tibial fixation. Multiplanar reformatted images of 3-T MRI scans were obtained at the 1st postoperative day before weight bearing is initiated in all patients to evaluate the gap (the tunnel–graft gap) between the top of the hamstring graft and top of the femoral tunnel. Postoperative MRI scans showed that the tunnel–graft gap was 1.5 ± 2.7 mm (range, 0–12 mm). In 43 (69.4%) patients, there was no gap between the top of the femoral tunnel and hamstring graft. In 19 (30.6%) patients, there was a gap between the tunnel and graft, and nine patients demonstrated a tunnel–graft gap greater than 5 mm. Immediate postoperative MRI scans demonstrated that an adjustable-loop cortical suspension device may not pull the hamstring graft completely into the femoral tunnel.
Keywords: hamstring graft; femoral tunnel; adjustable loop; MRI